2011
DOI: 10.1590/s1516-14392011005000096
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of reinforcing bars embedded in alkali-activated slag concrete subjected to chloride attack

Abstract: Steel bar embedded in an alkali-activated slag (AAS) concrete was tested under complete immersion, in 3.5% NaCl solution by weight of the slag. Ordinary Portland cement (OPC) was also tested for comparative purposes and exposed to the same solution. Monitoring of open-circuit potential, polarization resistance measurement and electrochemical impedance spectroscopy (EIS) were used to evaluate the corrosion behavior of steel bar. The corrosion resistances of AAS and OPC concretes were performed at 0, 3, 6, 9 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Electrochemical measurements indicated 10% corrosion possibility for both AAS and OPC concrete before immersing the specimens. On the other hand, the authors [34] illustrated 90% corrosion probability after 3-month immersion period in which active potential was ranging from À0.2 V to À0.6 V. They [34] concluded that due to the presence of chloride in the interface of steel and AAS, these phenomena occurred.…”
Section: Authormentioning
confidence: 98%
See 4 more Smart Citations
“…Electrochemical measurements indicated 10% corrosion possibility for both AAS and OPC concrete before immersing the specimens. On the other hand, the authors [34] illustrated 90% corrosion probability after 3-month immersion period in which active potential was ranging from À0.2 V to À0.6 V. They [34] concluded that due to the presence of chloride in the interface of steel and AAS, these phenomena occurred.…”
Section: Authormentioning
confidence: 98%
“…Miranda et al [22] Corrosion resistance NaOH and Na 2 SiO 3 FA Palacios and Puertas [23] Carbonation NaOH and Na 2 SiO 3 GBFS Fernandez-Jimenez et al [24] Acid attack and sulphate resistance NaOH and Na 2 SiO 3 FA Al-Otaibi [25] Chloride penetration resistance, porosity, carbonation Ca(OH) 2 and Na 2 SiO 3 GBFS Thokchom et al [26] Acid attack NaOH and Na 2 SiO 3 FA Wallah [27] Drying shrinkage NaOH and Na 2 SiO 3 FA Bernal et al [28] Carbonation and sorptivity NaOH and Na 2 SiO 3 GBFS and MK Allahverdi et al [29] Drying shrinkage NaOH and Na 2 SiO 3 GBFS Wongpa et al [30] Water permeability NaOH and Na 2 SiO 3 RHA and FA Yang et al [31] Shrinkage strain Ca(OH) 2 and Na 2 SiO 3 GBFS El-Sayed et al [7] Sulphate resistance NaOH and Na 2 SiO 3 GBFS Kushal and Partha [32] Porosity, water absorption and sorptivity NaOH and Na 2 SiO 3 FA Al Bakri et al [33] Acid resistance NaOH and Na 2 SiO 3 FA Chaparro et al [34] Corrosion resistance NaOH and Na 2 SiO 3 GBFS Beemamol et al [35] Chloride permeability and shrinkage NaOH FA Bernal et al [36] Carbonation NaOH and Na 2 SiO 3 GBFS and FA Prabu et al [37] Acid resistance, sulphate attack and chloride penetration NaOH, KOH, K 2 SiO 3 and Na 2 SiO 3 RHA and FA Shaikh [38] Chloride penetration, sorptivity and corrosion resistance NaOH and Na 2 SiO 3 FA Karim et al [39] Porosity, water absorption and thermal resistance NaOH GBFS, POFA and RHA FA: fly ash; GBFS: granulated blast furnace slag; MK: metakaolin; RHA: rice husk ash; POFA: palm oil fuel ash.…”
Section: Authormentioning
confidence: 99%
See 3 more Smart Citations